We are victims! How observers evaluate a group's claim of collective victimhood. Issue 12 (8th October 2018) - Belavadi, Sucharita; Hogg, Michael A.
Abstract: Intergroup relations often involve a competitive narrative revolving around claims of collective victimhood. This article investigates how the communication of such claims impacts third‐party perceptions of the group's structure and future actions. Two experiments explored the underlying processes that shape such third‐party perceptions. Study 1 ( N  = 86) showed that victim‐claiming groups were perceived as more uncertain than groups not claiming victimhood and as a result as less entitative units. Study 2 ( N  = 165) showed that victimhood‐claiming groups' intentions toward violent and retributive acts were legitimized by observers through perceptions of heightened uncertainty. Claims of collective victimhood help groups justify the adoption of a violent strategy against an antagonistic outgroup through perceived heightened uncertainty. Further, Study 2 showed that power moderated the relationship between victimhood claims by groups and the perceived entitativity of such groups—low‐power groups communicating a message of victimhood were perceived as more entitative than low‐power groups not making such claims. Implications of third‐party perceptions of conflicting groups on already troubled intergroup relations are discussed.